Composite, catalyst ink, and method for producing the composite
A composite of molybdenum disulfide and trioxide with optimized properties and low-temperature sulfurization addresses performance limitations in hydrogen generation catalysts, improving catalytic activity for water electrolysis.
Patent Information
- Application Number
- JP2024521304
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2023-09-15
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-09-15
AI Technical Summary
Existing catalyst materials containing molybdenum disulfide do not achieve the expected performance for hydrogen generation, particularly in water electrolysis, due to limitations in composition and structure.
A composite of molybdenum disulfide and molybdenum trioxide with specific crystallite sizes, surface areas, and elemental ratios is developed, along with a method involving low-temperature sulfurization to enhance catalytic activity.
The composite exhibits improved catalytic performance for hydrogen generation, particularly in water electrolysis, by optimizing the interface between molybdenum disulfide and trioxide, enhancing active sites and catalytic efficiency.
Smart Images

Figure 0007605374000002 
Figure 0007605374000003 
Figure 0007605374000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite, a catalyst ink, and a method for making the composite. This application claims priority based on Japanese Patent Application No. 2022-146943, filed in Japan on September 15, 2022, the contents of which are incorporated herein by reference. [Background technology]
[0002] Water electrolysis technology is attracting attention as a technology that can produce hydrogen from water using renewable energy electricity, with the aim of resolving environmental and energy resource issues. Layered transition metal chalcogen compounds, such as molybdenum disulfide (MoS2), are expected to be materials with high catalytic activity while being inexpensive and abundant in resources.
[0003] Although it is possible to increase such catalytic activity to a certain extent by micronizing or deagglomerating molybdenum sulfide obtained by any production method such as sulfurizing molybdenum oxide, in many cases, the expected performance cannot be obtained by this alone. Therefore, in order to achieve better performance according to each intended use, methods for producing molybdenum sulfides with unique shapes, such as single-layer, nanoflower, and fullerene-like shapes, have been investigated (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-277199 A [Patent Document 2] Special Publication No. 2004-512250 Summary of the Invention [Problem to be solved by the invention]
[0005] However, there is still room for improvement in providing new catalytic materials containing molybdenum disulfide. The present invention aims to provide a composite, a catalyst ink, and a method for producing the composite that can be used as a catalyst, in particular as a hydrogen generation catalyst. [Means for solving the problem]
[0006] The present invention has the following aspects.
[0007] <1> A composite material comprising molybdenum disulfide and molybdenum trioxide, the molybdenum disulfide comprises a 3R crystal structure; A composite, in which the content of molybdenum trioxide equivalent (B) calculated from the molybdenum content determined by XRF analysis of the composite is 5 to 90 mass % relative to the total mass of the composite. <2> The molybdenum disulfide has an average crystallite size of 50 nm or less, determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement. <1> The complex according to claim 1, <3> The molybdenum trioxide has an average crystallite size of 50 nm or less, determined from a peak at 2θ=12.7°±0.5 obtained by X-ray diffraction measurement. <1> or <2> The complex according to claim 1, <4> The median diameter D of the complex is determined by dynamic light scattering. 50 is 1000 nm or less. <1> ~ <3> 2. The complex according to claim 1 , <5> The specific surface area of the composite, as measured by the BET method, is 5 m 2 / g or more 200m 2 / g or less. <1> ~ <4> 2. The complex according to claim 1 , <6> the ratio (A / B) of the molybdenum disulfide equivalent value (A) calculated from the sulfur content of the composite determined by XRF analysis to the molybdenum trioxide equivalent value (B) calculated from the molybdenum content of the composite determined by XRF analysis is 0.1 to 50 on a mass basis; <1> ~ <5> 2. The complex according to claim 1 , <7> The molybdenum disulfide equivalent value (A) calculated from the sulfur content of the composite determined by XRF analysis is 10 to 95 mass% relative to the total mass of the composite. <1> ~ <6> 2. The complex according to claim 1 , <8> The ratio of the content of sulfur as an element to the total content of sulfur element in the complex is 10% or less on a molar basis. <1> ~ <7> 2. The complex according to claim 1 , <9> The above-mentioned compound is used as a hydrogen generating catalyst. <1> ~ <8> 2. The complex according to claim 1 , <10> The above <1> ~ <9> 13. A catalyst ink comprising the composite according to any one of claims 1 to 12 and a solvent. <11> The method includes a calcination step of heating molybdenum trioxide in the presence of a sulfur source at a temperature of 400° C. or less. <1> ~ <9> 13. A method for producing the complex according to any one of the preceding claims. <12> The calcination step is followed by a washing step for removing the sulfur source. <11> A method for producing the complex described above. <13> The specific surface area of the molybdenum trioxide measured by the BET method is 10 m 2 / g or more 100m 2 / g or less. <11> or <12> A method for producing the complex described above. Effect of the Invention
[0008] According to the present invention, it is possible to provide a composite, a catalyst ink, and a method for producing the composite that can be used as a catalyst, in particular as a hydrogen generation catalyst. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of an apparatus used for producing molybdenum trioxide particles that can be used as a raw material for the composite of the embodiment. [Diagram 2] FIG. 1 is a diagram showing X-ray diffraction (XRD) profiles of the particles obtained in Examples 1 to 5 and Reference Example 1 superimposed on each other. [Diagram 3] 1 is a transmission electron microscope (TEM) image of the composite particles obtained in Example 1. [Figure 4] 1 shows an image of the composite particles obtained in Example 1, taken with a High-Angle Annular Dark Field Scanning TEM (HAADF-STEM), and an image showing the results of elemental mapping by energy dispersive X-ray spectroscopy (EDS). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the composite, catalyst ink, and method for producing the composite of the present invention will be described.
[0011] <Complex> The composite of the embodiment is a composite containing molybdenum disulfide and molybdenum trioxide, wherein the molybdenum disulfide has a 3R crystal structure, and a molybdenum trioxide equivalent value (B) calculated from a molybdenum content determined by XRF analysis of the composite is 5 to 90 mass% relative to the total mass of the composite.
[0012] An embodiment composite includes both molybdenum disulfide (MoS2) and molybdenum trioxide (MoO3). The composite contains MoS2 and MoO3, and the catalytic performance is improved due to the exchange of electrons at the interface between MoS2 and MoO3.
[0013] In addition, the molybdenum disulfide in the composite of the embodiment contains a 3R crystal structure, which contributes to improving the catalytic performance. The crystal structure of molybdenum disulfide will be described in detail later.
[0014] As will be shown in the examples described later, composite particles containing molybdenum disulfide and molybdenum trioxide have improved catalytic performance as a hydrogen generation catalyst compared to particles containing only molybdenum disulfide, particles containing only molybdenum trioxide, or particles containing both but not satisfying the above-mentioned molybdenum trioxide equivalent value (B).
[0015] The form of MoS2 and MoO3 in the composite of the embodiment is not particularly limited, but according to the analysis results of energy dispersive X-ray spectroscopy (EDS) shown in the examples described later, it has been confirmed that the content of S element is higher than that of O element in the region closer to the surface of the composite particle.
[0016] For this reason, the composite of the embodiment may have MoS2 unevenly distributed on the surface of the composite. The term "MoS2 unevenly distributed on the surface of the composite" refers to a state in which MoS2 is distributed more on the surface of the composite than inside the composite. Also, the composite may have a state in which MoO3 is distributed less on the surface of the composite than inside the composite.
[0017] The composite of the embodiment contains molybdenum disulfide (MoS2). The composite of the embodiment contains molybdenum disulfide (MoS2) in an amount of preferably 10 to 95 mass%, more preferably 15 to 50 mass%, and even more preferably 20 to 45 mass%, based on the total mass (100 mass%) of the composite.
[0018] The content of molybdenum disulfide (MoS2) in the composite of the embodiment may be a value calculated by the following XRF analysis.
[0019] In the composite of the embodiment, the molybdenum disulfide equivalent value (A) calculated from the sulfur content determined by XRF analysis of the composite is preferably 10 to 95 mass%, more preferably 15 to 50 mass%, and even more preferably 20 to 45 mass%, relative to the total mass of the composite. A composite having a molybdenum disulfide equivalent content (A) within the above range has a good molybdenum sulfide content, and the catalytic activity derived from the molybdenum sulfide is more effectively exhibited.
[0020] The molybdenum disulfide equivalent value (A) refers to the value obtained from the amount of MoS2 obtained by converting the sulfur content determined by XRF analysis of the composite using a calibration curve for MoS2 conversion.
[0021] The composite of the embodiment contains molybdenum trioxide (MoO3). The composite of the embodiment may contain 5 to 90 mass% of molybdenum trioxide (MoO3) relative to the total mass (100 mass%) of the composite, more preferably 50 to 85 mass%, and even more preferably 55 to 80 mass%.
[0022] The content of molybdenum trioxide (MoO3) in the composite of the embodiment may be a value calculated by the following XRF analysis.
[0023] In the composite of the embodiment, the content of molybdenum trioxide equivalent value (B) calculated from the molybdenum content determined by XRF analysis of the composite is 5 to 90 mass%, preferably 50 to 85 mass%, and more preferably 55 to 80 mass% relative to the total mass of the composite. A composite having a molybdenum trioxide equivalent content (B) within the above range has a good molybdenum oxide content, and the catalytic activity derived from the molybdenum oxide is more effectively exhibited.
[0024] The molybdenum trioxide equivalent value (B) refers to the value obtained from the amount of MoO3 converted from the molybdenum content determined by XRF analysis of the complex using a calibration curve for MoO3 conversion. In the composite of the embodiment, molybdenum is also contained as MoS2, so the MoS2 equivalent is first calculated as described above, and the amount of molybdenum remaining after subtracting the molybdenum equivalent of the MoS2 value is used to calculate the molybdenum trioxide equivalent value (B).
[0025] In the composite of the embodiment, the content in terms of molybdenum disulfide (A) relative to the total mass of the composite may preferably be 10 to 95 mass%, and the content in terms of molybdenum trioxide (B) relative to the total mass of the composite may preferably be 5 to 90 mass%. In the composite of the embodiment, more preferably, the content in terms of molybdenum disulfide (A) relative to the total mass of the composite may be 15 to 50 mass%, and the content in terms of molybdenum trioxide (B) relative to the total mass of the composite may be 50 to 85 mass%. In the composite of the embodiment, more preferably, the content in terms of molybdenum disulfide (A) relative to the total mass of the composite may be 20 to 45 mass%, and the content in terms of molybdenum trioxide (B) relative to the total mass of the composite may be 55 to 80 mass%.
[0026] The ratio (A / B) of the molybdenum disulfide equivalent value (A) calculated from the sulfur content of the composite obtained by XRF analysis to the molybdenum trioxide equivalent value (B) calculated from the molybdenum content of the composite obtained by XRF analysis is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.25 or more, and particularly preferably 0.3 or more, on a mass basis. Moreover, the ratio (A / B) is preferably 50 or less, more preferably 25 or less, even more preferably 3 or less, and particularly preferably less than 1. An example of the range of the ratio (A / B) may be 0.1 or more and 50 or less, 0.2 or more and 25 or less, 0.25 or more and 3 or less, or 0.3 or more and less than 1. A composite having the ratio (A / B) within the above range has an excellent balance of the content ratio of molybdenum oxide and molybdenum sulfide, and has an appropriate amount of interfaces that contribute to catalytic activity, allowing the composite to exhibit catalytic activity more effectively.
[0027] The average crystallite size of the molybdenum disulfide contained in the composite, as determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement, is preferably 50 nm or less, more preferably 40 nm or less, more preferably 30 nm or less, even more preferably 20 nm or less, particularly preferably 10 nm or less, and particularly preferably less than 6 nm. The above peak at 2θ=14.4°±0.5° is attributed to the (002) or (003) plane of molybdenum disulfide (MoS2). By including MoS2 with a small average crystallite size, such as the upper limit value or less, the number of catalytically active sites such as interfaces and defects that contribute to catalytic activity increases, improving catalytic performance.
[0028] The lower limit of the average crystallite size of the molybdenum disulfide determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement may be, for example, 1 nm or more, 2 nm or more, or 3 nm or more.
[0029] An example of the numerical range of the average crystallite size of the molybdenum disulfide calculated from the peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement may be 1 nm or more and 50 nm or less, 2 nm or more and 40 nm or less, 2 nm or more and 30 nm or less, 3 nm or more and 20 nm or less, 3 nm or more and 10 nm or less, or 3 nm or more and less than 6 nm.
[0030] The molybdenum trioxide contained in the composite has an average crystallite size, determined from a peak at 2θ=12.7°±0.5° obtained by X-ray diffraction measurement, of preferably 50 nm or less, more preferably 40 nm or less, even more preferably 30 nm or less, and particularly preferably 20 nm or less. The above peak at 2θ=12.7°±0.5° is attributed to the (020) plane of molybdenum trioxide (MoO3). By including MoO3 with a small average crystallite size, such as the upper limit value above, the number of catalytically active sites such as interfaces and defects that contribute to catalytic activity increases, improving catalytic performance.
[0031] The lower limit of the average crystallite size of the molybdenum trioxide determined from a peak at 2θ=12.7°±0.5° obtained by X-ray diffraction measurement may be, for example, 1 nm or more, 2 nm or more, or 3 nm or more.
[0032] An example of the numerical range of the average crystallite size of the molybdenum trioxide determined from the peak at 2θ=12.7°±0.5° obtained by X-ray diffraction measurement may be 1 nm or more and 50 nm or less, 2 nm or more and 40 nm or less, 3 nm or more and 30 nm or less, or 3 nm or more and 20 nm or less.
[0033] The average crystallite size in the composite of the embodiment can be determined by the following measurement method.
[0034] [Crystallite size measurement] An X-ray diffraction apparatus (e.g., SmartLab 9kW, manufactured by Rigaku Corporation) is used, a scintillation counter is used as a detector, and analysis software (e.g., PDXL2) is used to perform the measurement. The measurement method is the 2θ / θ method, and the average crystallite size is calculated using the Scherrer equation from the half-width of the peak that appears in the corresponding range of 2θ=14.4°±0.5° or the range of 2θ=12.7°±0.5°. The measurement conditions are a scan speed (2θ) of 2.0° / min, a scan range (2θ) of 10 to 70°, a step (2θ) of 0.02°, and no standard width of the apparatus.
[0035] The composite of the embodiment may be a particulate structure (composite particle).
[0036] The median diameter D of the complex of the embodiment measured by dynamic light scattering 50 is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 600 nm or less. The median diameter D 50 A composite having a molecular weight of 100 or less can more effectively exhibit catalytic efficiency.
[0037] The median diameter D of the complex of the embodiment measured by dynamic light scattering 50 For example, it may be 20 nm or more, 40 nm or more, 100 nm or more, or 300 nm or more.
[0038] The median diameter D of the complex of the embodiment measured by dynamic light scattering 50 An example of the numerical range of the above numerical value may be 20 nm or more and 1000 nm or less, 40 nm or more and 800 nm or less, 100 nm or more and 600 nm or less, or 300 nm or more and 600 nm or less.
[0039] The median diameter D of the composite of the embodiment calculated by dynamic light scattering method 50 can be determined as the particle size at which the volume cumulative percentage is 50% in the particle size distribution measured in wet condition using a dynamic light scattering particle size distribution analyzer (e.g., Nanotrac WaveII, manufactured by Microtrack-Bell) with acetone as the medium.
[0040] The specific surface area of the composite of the embodiment measured by the BET method is 5 m 2 / g or more, and 2 / g or more is more preferable, and 15m 2 More preferably, it is 20m 2 It is particularly preferable that the molecular weight is 1 / g or more. A composite having a specific surface area equal to or greater than the above lower limit has a large specific surface area, which increases the number of catalytically active sites and facilitates material transfer in the reaction system, thereby enabling the catalytic efficiency to be improved more effectively.
[0041] The specific surface area of the composite of the embodiment measured by the BET method is, for example, 200 m 2 / g or less, and 2 / g or less.
[0042] An example of the range of the specific surface area of the composite of the embodiment measured by the BET method is 5 m 2 / g or more 200m 2 / g or less, 2 / g or more 200m 2 / g or less, 2 / g or more 100m2 / g or less, 2 / g or more 100m 2 / g or less.
[0043] In this specification, the specific surface area is measured using a specific surface area meter (e.g., BELSORP-mini manufactured by Microtrack-Bell Co., Ltd.), and the surface area per 1 g of a sample measured from the amount of nitrogen gas adsorbed by the BET method (Brunauer-Emmett-Teller method) is defined as the specific surface area (m 2 / g).
[0044] The ratio of the content of sulfur as an element to the total content of sulfur element in the complex (100%) is preferably 10% or less, and more preferably 5% or less, on a molar basis.
[0045] The composite of the embodiment can be provided as an aggregate (for example, powder) of composite particles. If the aggregate contains molybdenum disulfide (MoS2), MoS x (X=1 to 3). Similarly, if the aggregate contains molybdenum trioxide (MoO3), it may contain one or more kinds of molybdenum sulfides represented by the formula: MoO2 or Mo9O 25 The molybdenum oxide may contain one or more kinds of molybdenum oxide represented by the following formula:
[0046] Also, for example, the above average crystallite size, D 50 , specific surface area, XRF analysis, conversion rate R C The values relating to can be values measured using an aggregate of composite particles (for example, powder) as a sample.
[0047] Conversion rate R of the composite of the embodiment to MoS C is preferably 90% or less, more preferably 60% or less, and even more preferably 50% or less. The conversion rate to MoS2 R C When the amount of the catalyst is equal to or less than the upper limit, the catalyst performance can be more effectively exhibited. Conversion rate R of the composite of the embodiment to MoS C is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. The conversion rate to MoS2 R C When the above lower limit value or more is satisfied, the catalytic performance can be more effectively exhibited. The conversion rate R of the composite of the embodiment C An example of the above-mentioned numerical range is the conversion rate R C may be 10% or more and 90% or less, may be 15% or more and 60% or less, or may be 20% or more and 50% or less.
[0048] Conversion rate R of the composite of the embodiment to MoS C The RIR value K of molybdenum disulfide (MoS2) can be obtained by the RIR (reference intensity ratio) method from profile data obtained by subjecting the composite of the embodiment to X-ray diffraction (XRD) measurement. A and the integrated intensity I of the peak at 2θ=14.4°±0.5°, which is assigned to the (002) or (003) plane of molybdenum disulfide (MoS2). A , and each molybdenum oxide (the raw material MoO3 and the reaction intermediate Mo9O 25 , Mo4O 11 , MoO2, etc.) RIR value K B and each molybdenum oxide (the raw material MoO3 and the reaction intermediate Mo9O 25 , Mo4O 11 , MoO2, etc.) B Using the above, the conversion rate R to MoS2 is calculated from the following equation (1): C can be sought. R C (%)=(I A / K A ) / ((I A / K A )+Σ(I B / K B ))×100 (1) Here, the RIR values can be those listed in the Inorganic Crystal Structure Database (ICSD) (manufactured by the Japan Chemical Information Association), and integrated powder X-ray analysis software (e.g., PDXL2, manufactured by Rigaku Corporation) can be used for the analysis.
[0049] The crystal structure of the molybdenum trioxide contained in the composite of the embodiment may include α crystals, or may include α crystals and β crystals.
[0050] In the composite of the embodiment, the α crystal structure of molybdenum trioxide can be confirmed by the presence of a peak in the (021) plane of the α crystal of MoO3 (2θ: around 27.32°, No. 166363 (Inorganic Crystal Structure Database, ICSD)). Also, the β crystal structure can be confirmed by the presence of a peak (2θ: around 23.01°, No. 86426 (Inorganic Crystal Structure Database, ICSD)) which belongs to the (011) plane of the β crystal of MoO3 in a profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as the X-ray source.
[0051] In the composite of the embodiment, in a profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as an X-ray source, it is preferable that the ratio of the peak intensity attributable to the (011) plane of the β crystal of MoO3 to the peak intensity attributable to the (021) plane of the α crystal of MoO3 (β(011) / α(021)) is 0.1 or more.
[0052] For the peak intensity attributable to the (011) plane of the β crystal of MoO3 and the peak intensity attributable to the (021) plane of the α crystal of MoO3, the maximum peak intensity is read and the ratio (β(011) / α(021)) is calculated.
[0053] In the MoO3 of the composite of the embodiment, the ratio (β(011) / α(021)) is preferably 0.1 to 10.0, more preferably 0.2 to 10.0, and particularly preferably 0.4 to 10.0.
[0054] The content of α-crystals of MoO3 in the composite of the embodiment is not particularly limited, but may be 20% or more, 50% or more, 70% or more, 80% or more, or 100%.
[0055] In a mixture of α and β crystals of MoO3, the content of α crystals of MoO3 can be determined from the obtained profile data by the RIR (reference intensity ratio) method. The RIR value K of α crystals of MoO3 is A and the integrated intensity I of the (021) plane of the α crystal of MoO3 (2θ: around 27.32°_No. 166363 (Inorganic Crystal Structure Database, ICSD)) A , and the RIR value K of MoO3 β crystal B and the integrated intensity I of (011) plane of MoO3 β crystal (2θ: around 23.01°, No. 86426 (Inorganic Crystal Structure Database, ICSD)). B Using this, the content (%) of α crystals in MoO3 can be calculated from the following formula (2). MoO3 α crystal content (%) = (I A / K A ) / ((I A / K A )+(I B / K B ))×100 (2) Here, the RIR values can be those listed in the ICSD database, and the analysis can be performed using integrated powder X-ray analysis software (PDXL2, manufactured by Rigaku Corporation).
[0056] The molybdenum disulfide contained in the composite of the embodiment includes a 3R crystal structure, and may include a 2H crystal structure and a 3R crystal structure. The composite of the embodiment including such a 2H crystal structure and a 3R crystal structure is a product uniquely developed by the present applicant, and has not only a 2H crystal structure but also a rare 3R (rhombohedral) structure. Since the 3R structure tends to have a distorted crystal structure and has more catalytically active sites, the inclusion of the 3R crystal structure in molybdenum disulfide contributes to improving catalytic performance.
[0057] The complex containing the 3R crystal structure can be produced, for example, by the <<Composite Production Method>> described below. It is possible to synthesize molybdenum disulfide that contains the 3R structure and is advantageous for achieving a large surface area on the nm scale, which is difficult to achieve by crushing mine products or synthesis from general-purpose molybdenum trioxide.
[0058] The abundance ratio of the 3R crystal structure in the crystal phase of molybdenum disulfide may be 5% or more and 60% or less, 10% or more and 60% or less, 20% or more and 60% or less, or 20% or more and 45% or less.
[0059] The fact that molybdenum disulfide has a 2H crystal structure and a 3R crystal structure can be confirmed, for example, by using an extended Rietveld analysis software (High Score Plus, manufactured by Malvern Panalytical) that can take into account the crystallite size. In this Rietveld analysis software, the entire XRD diffraction profile is simulated using a crystal structure model including the crystallite size, and compared with the XRD diffraction profile obtained by experiment, and the crystal lattice constant of the crystal structure model, crystal structure factors such as atomic coordinates, weight fraction (abundance ratio), etc. are optimized by the least squares method so that the residual between the diffraction profile obtained by experiment and the diffraction profile obtained by calculation is minimized, and each phase of the 2H crystal structure and the 3R crystal structure is identified and quantified with high accuracy, and in addition to the crystal structure type and its ratio calculated by normal Rietveld analysis, the crystallite size can be calculated. Hereinafter, in this specification, the analysis method using the above-mentioned High Score Plus is referred to as "Extended Rietveld analysis".
[0060] In addition, in the composite of the embodiment, the crystallite size of the 3R crystal structure obtained by extended Rietveld analysis using the profile obtained from the XRD may be 1 nm or more and 50 nm or less, and preferably consists of a crystalline phase composed of crystallites having a size of 5 nm or more and 50 nm or less, and more preferably the crystallite size is 10 nm or more and 40 nm or less.
[0061] In addition, in the composite of the embodiment, the crystallite size of the 2H crystal structure obtained by extended Rietveld analysis using the profile obtained from the XRD is preferably 1 nm or more and 50 nm or less, and the crystalline phase is preferably composed of crystallites having sizes of 1 nm or more and 50 nm or less, and more preferably the crystallite size is 5 nm or more and 50 nm or less.
[0062] The 2H crystal structure obtained by the extended Rietveld analysis is preferably composed of a single crystal phase composed of crystallites having a predetermined crystallite size, and in this case, the crystallite size of the 2H crystal structure is more preferably 1 nm to 20 nm, more preferably 5 nm to 15 nm.
[0063] The crystallite size of the 2H crystal structure and the crystallite size of the 3R crystal structure can also be calculated using, for example, the peak half-width of an XRD diffraction profile.
[0064] The abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure in the crystal phase, which is obtained by extended Rietveld analysis using the profile obtained from the XRD, is preferably 10:90 to 90:10.
[0065] The abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure in the crystal phase, which is obtained by extended Rietveld analysis using the profile obtained from the XRD, is more preferably 10:90 to 80:20, and further preferably 40:60 to 80:20, from the viewpoint of the above-mentioned effects.
[0066] The 2H crystal structure obtained by the extended Rietveld analysis may be composed of a first crystal phase composed of crystallites having a predetermined crystallite size, and a second crystal phase having a smaller crystallite size than the first crystal phase. The crystallite size of the first crystal phase of the 2H crystal structure is, for example, greater than 20 nm and less than 150 nm, and may be 50 nm or more and 150 nm or less, or may be 100 nm or more and 150 nm or less. However, it is preferable that the first crystal phase does not exist in the crystal phase of the 2H crystal structure, or that the abundance ratio of the first crystal phase is low. The crystallite size of the second crystal phase of the 2H crystal structure is preferably 1 nm or more and 20 nm or less, and may be 1 nm or more and 10 nm or less, or may be 5 nm or more and 15 nm or less.
[0067] The crystallite size of the first crystal phase of the 2H crystal structure, the crystallite size of the 3R crystal structure, and the crystallite size of the second crystal phase of the 2H crystal structure can also be calculated using, for example, the half-width of the peaks in the XRD diffraction profile, as described above.
[0068] The abundance ratio of the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure in the crystal phase (2H (first crystal phase):3R:2H (second crystal phase)) obtained by extended Rietveld analysis using the profile obtained from the XRD is preferably 30-0:10-70:80-15, and more preferably 25-0:20-60:75-20.
[0069] In a profile obtained by powder X-ray diffraction (XRD) of the composite of the embodiment using Cu-Kα radiation as an X-ray source, the peaks near 2θ=39.5° and 49.5° are derived from the 2H crystal structure, and the peaks near 2θ=32.5°, 39.5°, and 49.5° are derived from the 3R crystal structure, and the half-widths of the peaks near 2θ=39.5° and 49.5° are preferably 1° or more. Furthermore, the molybdenum disulfide may include a crystal structure other than the 2H crystal structure and 3R crystal structure of molybdenum disulfide, such as a 1H crystal structure.
[0070] The fact that the molybdenum disulfide contains a metastable 3R crystal structure can be distinguished by the fact that in a profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as an X-ray source, both of the peaks at around 2θ=39.5° and 2θ=49.5° are composite peaks of the 2H crystal structure and the 3R crystal structure.
[0071] In practice, the abundance ratio of the 2H crystal structure is determined by the peak near 2θ=39.5° and the broad peak near 49.5° using the profile obtained from the powder X-ray diffraction (XRD). The abundance ratio of the 3R crystal structure is determined by optimizing the difference between the peak near 2θ=39.5° and the broad peak near 49.5° with two peaks near 2θ=32.5° and two peaks near 39.5°. That is, both the peak near 2θ=39.5° and the peak near 49.5° are composite waves derived from the 2H crystal structure and the 3R crystal structure, and the abundance ratio of the 2H crystal structure and the 3R crystal structure of molybdenum disulfide can be calculated by these composite waves.
[0072] The composite of the embodiment may also contain an amorphous phase. The ratio of the amorphous phase in the composite of the embodiment is expressed as 100(%)-(crystallinity(%)), and is preferably 5% or more, more preferably 15% or more, and even more preferably 20% or more.
[0073] In the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) profile at the molybdenum K absorption edge of the composite of the embodiment, the ratio (I / II) of the peak intensity I due to Mo-S to the peak intensity II due to Mo-Mo is preferably greater than 1.0, more preferably 1.1 or more, and particularly preferably 1.2 or more.
[0074] Whether the crystal structure of molybdenum disulfide is a 2H crystal structure or a 3R crystal structure, the distance between Mo-S is almost the same due to covalent bonds, so the intensity of the peak due to Mo-S is the same in the extended X-ray absorption fine structure (EXAFS) profile at the K absorption edge of molybdenum. On the other hand, since the 2H crystal structure of molybdenum disulfide is hexagonal, the same hexagon is located 90° directly below the hexagon of the Mo atom, so the distance between Mo-Mo is closer and the peak intensity II due to Mo-Mo is stronger. Conversely, since the 3R crystal structure of molybdenum disulfide is rhombohedral, the hexagon is not directly below the hexagon at 90° but is shifted by half an angle, which increases the distance between Mo-Mo and weakens the peak intensity II due to Mo-Mo. In the pure 2H crystal structure of molybdenum disulfide, the ratio (I / II) is small, but as it contains the 3R crystal structure, the ratio (I / II) becomes larger.
[0075] The composite of the embodiment described above can exhibit excellent catalytic performance.
[0076] The composite of the embodiment can be used as a catalyst, and can be used as a hydrogen generation catalyst. The composite of the embodiment can be suitably used as a hydrogen generation catalyst in a hydrogen generation reaction (HER) such as water electrolysis. Furthermore, the composite of the embodiment can be suitably used as a constituent material of a catalyst ink capable of forming a catalyst layer. Moreover, the composite of the embodiment can be suitably used as an electrode material used as a constituent material of an electrode catalyst layer.
[0077] <Method for manufacturing the composite> [Firing process] The method for producing the composite of the embodiment includes a calcination step of heating molybdenum trioxide in the presence of a sulfur source at a temperature of 400° C. or less. The molybdenum trioxide preferably includes a β crystal structure.
[0078] In another aspect, the method for producing a composite of the embodiment may include, for example, a calcination step of heating the molybdenum trioxide particles obtained by the molybdenum trioxide particle production step described below in the presence of a sulfur source at a temperature of 400° C. or lower.
[0079] The method for producing the composite may include heating molybdenum trioxide particles containing a β crystal structure of molybdenum trioxide at a temperature of 100 to 800°C in the absence of a sulfur source, and then heating at a temperature of 400°C or less in the presence of a sulfur source.
[0080] The calcination temperature in the presence of a sulfur source in the calcination step is 400° C. or lower, preferably less than 350° C., more preferably 320° C. or lower, and even more preferably 310° C. or lower. The firing temperature may be, for example, 200°C or higher and 400°C or lower, 220°C or higher and lower than 350°C, or 220°C or higher and lower than 320°C, and is more preferably 250°C or higher and 310°C or lower. By setting the firing temperature at a low temperature of 400° C. or less, the progress of the sulfurization reaction from molybdenum trioxide to molybdenum disulfide can be easily controlled, and a composite containing both molybdenum disulfide and molybdenum trioxide can be easily obtained.
[0081] The calcination time in the presence of a sulfur source may be any time that allows the sulfurization reaction to proceed appropriately and allows both molybdenum disulfide and molybdenum trioxide to coexist, and may be 1 to 20 hours, 2 to 15 hours, or 3 to 10 hours.
[0082] The calcination temperatures and calcination times exemplified above may be freely combined, and examples of the calcination conditions in the presence of a sulfur source in the calcination step include a condition in which a calcination temperature is maintained at 200° C. or more and 400° C. or less for 1 to 20 hours, a condition in which a calcination temperature is maintained at 220° C. or more and less than 350° C. for 2 to 15 hours, a condition in which a calcination temperature is maintained at 220° C. or more and 320° C. or less for 3 to 10 hours, and a condition in which a calcination temperature is maintained at 250° C. or more and 310° C. or less for 3 to 10 hours.
[0083] The rate of temperature rise up to the firing temperature is preferably 1° C. / min or more and 50° C. / min or less, and more preferably 2° C. / min or more and 10° C. / min or less.
[0084] The average particle size of the primary particles of the molybdenum trioxide is, for example, 2 nm or more and 1000 nm or less.
[0085] The molybdenum trioxide particles may have an average primary particle size of 5 nm or more and 2000 nm or less.
[0086] The average particle size of the primary particles of molybdenum trioxide particles refers to the average value of primary particle diameters of 50 randomly selected primary particles when molybdenum trioxide particles are photographed with a scanning electron microscope (SEM) or transmission electron microscope (TEM), and the long axis (the Feret diameter of the longest observed part) and short axis (the shorter Feret diameter perpendicular to the Feret diameter of the longest part) of the smallest unit particle (i.e., primary particle) that constitutes the aggregate in the two-dimensional image are measured, and the average value is taken as the primary particle diameter.
[0087] In the method for producing the composite, the molybdenum trioxide particles preferably have an average primary particle size of 1 μm or less. From the viewpoint of reactivity with sulfur, the average primary particle size is more preferably 600 nm or less, further preferably 400 nm or less, and particularly preferably 200 nm or less. The average primary particle size of the molybdenum trioxide particles may be 2 nm or more, 5 nm or more, or 10 nm or more.
[0088] The molybdenum trioxide particles used in the production of the composite preferably consist of an aggregate of primary particles containing the β crystal structure of molybdenum trioxide. The molybdenum trioxide particles have a better reactivity with sulfur than conventional molybdenum trioxide particles that are composed only of α crystals as a crystal structure, and because they contain the β crystal structure of molybdenum trioxide, the conversion rate R to MoS2 in the reaction with a sulfur source is higher. C can be made larger.
[0089] The β-crystal structure of molybdenum trioxide can be confirmed by the presence of a peak (2θ: around 23.01°, No. 86426 (Inorganic Crystal Structure Database (ICSD))) that belongs to the (011) plane of the β-crystal of MoO3 in the profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as the X-ray source. The α-crystal structure of molybdenum trioxide can be confirmed by the presence of a peak (2θ: around 27.32°, No. 166363 (Inorganic Crystal Structure Database (ICSD)))) that belongs to the (021) plane of the α-crystal of MoO3.
[0090] In a profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as an X-ray source, the molybdenum trioxide particles preferably have a ratio (β(011) / α(021)) of the peak intensity attributable to the (011) plane of a β crystal of MoO3 to the peak intensity attributable to the (021) plane of an α crystal of MoO3 (2θ: near 27.32°_No. 166363 (Inorganic Crystal Structure Database (ICSD))) of 0.1 or more.
[0091] For the peak intensity attributable to the (011) plane of the β crystal of MoO3 and the peak intensity attributable to the (021) plane of the α crystal of MoO3, the maximum peak intensity is read and the ratio (β(011) / α(021)) is calculated.
[0092] In the molybdenum trioxide particles, the ratio (β(011) / α(021)) is preferably from 0.1 to 10.0, more preferably from 0.2 to 10.0, and particularly preferably from 0.4 to 10.0.
[0093] The β crystal structure of molybdenum trioxide is observed at wavenumbers of 773 and 848 cm in the Raman spectrum obtained by Raman spectroscopy. -1 and 905 cm -1 The α-crystal structure of molybdenum trioxide can also be confirmed by the presence of peaks at wavenumbers 663 and 816 cm. -1 and 991 cm -1 This can be confirmed by the presence of a peak at
[0094] Examples of the sulfur source include sulfur and hydrogen sulfide, which may be used alone or in combination.
[0095] In the method for producing the composite, the molar ratio (sulfur (S) / molybdenum trioxide (MoO3)) of the amount of S in the sulfur source to the amount of MoO3 in the molybdenum trioxide particles may be in the range of 2 to 30, 3 to 15, or 4 to 6.
[0096] The greater the excess amount of the sulfur source, the more the amount of unreacted molybdenum oxide tends to be suppressed. On the other hand, as the above-mentioned firing temperature and firing time values are decreased, the amount of unreacted molybdenum oxide present tends to increase.
[0097] In the method for producing the composite, the molybdenum trioxide particles preferably have a MoO3 content of 99.5 mass% or more as measured by X-ray fluorescence (XRF). C It is possible to easily control the amount of disulfide produced, and it is possible to obtain a high-purity composite having excellent storage stability and no risk of producing disulfides derived from impurities.
[0098] The molybdenum trioxide particles have a specific surface area of 10 m as measured by the BET method. 2 / g~100m 2 It is preferred that the molecular weight is / g.
[0099] In the molybdenum trioxide particles, the specific surface area is 10 m because the reactivity with sulfur is good. 2 / g or more, and 2 / g or more is more preferable, and 30m 2 In the molybdenum trioxide particles, the particle size is preferably 100 m 2 / g or less, and 2 / g or less, 2 / g or less.
[0100] The molybdenum trioxide particles have a peak intensity I due to Mo-O and a peak intensity II due to Mo-Mo in the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) profile at the K absorption edge of molybdenum. O Ratio to (I O / II O ) is preferably greater than 1.1.
[0101] Intensity of the peak due to Mo-O I O , and Mo-Mo peak intensity II O The maximum intensity of the peaks was read, and the ratio (I O / II O ) is calculated. O / II O ) is considered to be a measure of whether the β crystal structure of MoO3 is obtained in the molybdenum trioxide particles, and the above ratio (I O / II O ) is larger, the reactivity with sulfur is higher.
[0102] In the molybdenum trioxide particles, the ratio (I O / II O ) is preferably from 1.1 to 5.0, may be from 1.2 to 4.0, or may be from 1.2 to 3.0.
[0103] According to the method for producing a composite of the embodiment described above, it is possible to produce the composite of the embodiment. The method for producing a composite of the embodiment has excellent advantages, such as 1) no need to use an organic solvent during the reaction, 2) unlike the general hydrothermal method, it is possible to recover the composite without performing an operation such as filtration, and 3) mass production is easy.
[0104] (Method of producing molybdenum trioxide particles) The method for producing the composite according to the embodiment may further include a molybdenum trioxide production step of producing the molybdenum trioxide particles.
[0105] The molybdenum trioxide particles may be produced by a molybdenum trioxide manufacturing process that includes vaporizing a molybdenum oxide precursor compound to form molybdenum trioxide vapor and cooling the molybdenum trioxide vapor.
[0106] The method for producing molybdenum trioxide particles includes calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound, and vaporizing the molybdenum oxide precursor compound to form molybdenum trioxide vapor, and it is preferable that the proportion of the metal compound relative to 100 mass% of the raw material mixture is 70 mass% or less, calculated as oxide.
[0107] The method for producing the molybdenum trioxide particles can be suitably carried out using a production apparatus 1 shown in FIG.
[0108] FIG. 1 is a schematic diagram showing an example of an apparatus used for producing molybdenum trioxide particles, which are a raw material for the composite according to this embodiment. As shown in FIG. 1, the manufacturing apparatus 1 includes a calcination furnace 2 for calcining a molybdenum trioxide precursor compound or the raw material mixture and vaporizing the molybdenum trioxide precursor compound, a cross-shaped cooling pipe 3 connected to the calcination furnace 2 for granulating the molybdenum trioxide vapor vaporized by the calcination, and a recovery device 4 as a recovery means for recovering the molybdenum trioxide particles granulated by the cooling pipe 3. At this time, the calcination furnace 2 and the cooling pipe 3 are connected via an exhaust port 5. In addition, the cooling pipe 3 has an opening adjustment damper 6 at the left end of an outside air intake port (not shown) and an observation window 7 at the upper end. The recovery device 4 is connected to an exhaust device 8 as a first blowing means. When the exhaust device 8 exhausts air, the internal gas of the recovery device 4 and the cooling pipe 3 is sucked in, and outside air is blown into the cooling pipe 3 from the opening adjustment damper 6 of the cooling pipe 3. That is, the exhaust device 8 performs a suction function, and thus air is passively blown to the cooling pipe 3. The production apparatus 1 may have an external cooling device 9, which makes it possible to arbitrarily control the cooling conditions for the molybdenum trioxide vapor generated from the firing furnace 2.
[0109] By opening the opening adjustment damper 6, air is taken in from the outside air intake port, and the molybdenum trioxide vapor vaporized in the baking furnace 2 is cooled in the air atmosphere and turned into molybdenum trioxide particles, thereby achieving the ratio (I O / II O ) can be made larger than 1.1, and the β crystal structure of MoO3 can be easily obtained in the molybdenum trioxide particles. When the molybdenum trioxide vapor is cooled using liquid nitrogen or the like in a nitrogen atmosphere with a low oxygen concentration, the oxygen vacancy density is increased, and the ratio (I O / II O ) is easily reduced.
[0110] The molybdenum oxide precursor compound is not particularly limited as long as it can form molybdenum trioxide vapor by firing it. Examples of the molybdenum oxide precursor compound include metallic molybdenum, molybdenum trioxide, molybdenum dioxide, molybdenum sulfide, ammonium molybdate, phosphomolybdic acid (HPMo 12 O 40 ), silicomolybdic acid (H4SiMo 12 O 40 ), aluminum molybdate, silicon molybdate, magnesium molybdate (MgMo n O 3n+1 (n=1-3)), sodium molybdate (Na2Mo n O 3n+1 (n=1-3)), titanium molybdate, iron molybdate, potassium molybdate (KMo n O 3n+1 (n=1~3)), zinc molybdate, boron molybdate, lithium molybdate (Li2Mo n O 3n+1(n=1 to 3), cobalt molybdate, nickel molybdate, manganese molybdate, chromium molybdate, cesium molybdate, barium molybdate, strontium molybdate, yttrium molybdate, zirconium molybdate, copper molybdate, etc. These molybdenum oxide precursor compounds may be used alone or in combination of two or more. The form of the molybdenum oxide precursor compound is not particularly limited, and may be, for example, a powder such as molybdenum trioxide, or a liquid such as an aqueous solution of ammonium molybdate, but is preferably a powder that is easy to handle and has good energy efficiency.
[0111] It is particularly preferable to use commercially available α-crystalline molybdenum trioxide as the molybdenum trioxide precursor compound. When ammonium molybdate is used as the molybdenum oxide precursor compound, it is converted to thermodynamically stable molybdenum trioxide by calcination, and the vaporized molybdenum oxide precursor compound becomes the molybdenum trioxide.
[0112] Molybdenum trioxide vapor can also be produced by firing a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound.
[0113] Of these, the molybdenum oxide precursor compound preferably contains molybdenum trioxide, in terms of ease of control of the purity, average primary particle size, and crystal structure of the resulting molybdenum trioxide powder.
[0114] There are cases where an intermediate is generated between a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound. Even in this case, the intermediate is decomposed by firing, and molybdenum trioxide can be vaporized in a thermodynamically stable form.
[0115] As the metal compound other than the molybdenum oxide precursor compound, it is preferable to use an aluminum compound among these in order to prevent damage to the firing furnace, and it is also possible not to use a metal compound other than the molybdenum oxide precursor compound in order to improve the purity of the molybdenum trioxide particles.
[0116] The metal compound other than the molybdenum oxide precursor compound is not particularly limited, and examples thereof include aluminum compounds, silicon compounds, titanium compounds, magnesium compounds, sodium compounds, potassium compounds, zirconium compounds, yttrium compounds, zinc compounds, copper compounds, iron compounds, etc. Among these, it is preferable to use the aluminum compounds, silicon compounds, titanium compounds, or magnesium compounds as the metal compound.
[0117] There are cases where an intermediate is generated between a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound. Even in this case, the intermediate is decomposed by calcination, and molybdenum trioxide can be vaporized in a thermodynamically stable form.
[0118] As the metal compound other than the molybdenum oxide precursor compound, it is preferable to use an aluminum compound in order to prevent damage to a firing furnace. In the production method, it is not necessary to use a metal compound other than the molybdenum oxide precursor compound in order to improve the purity of the molybdenum trioxide powder.
[0119] Examples of aluminum compounds include aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition aluminum oxides (such as γ-aluminum oxide, δ-aluminum oxide, and θ-aluminum oxide), α-aluminum oxide, and mixed aluminum oxides having two or more crystal phases.
[0120] When a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound is fired, the content of the molybdenum oxide precursor compound relative to 100 mass% of the raw material mixture is preferably 40 mass% or more and 100 mass% or less, may be 45 mass% or more and 100 mass% or less, or may be 50 mass% or more and 100 mass% or less.
[0121] The calcination temperature varies depending on the molybdenum oxide precursor compound, metal compound, desired molybdenum trioxide particles, etc., but is usually preferably set to a temperature at which the intermediate can be decomposed. For example, when a molybdenum compound is used as the molybdenum oxide precursor compound and an aluminum compound is used as the metal compound, aluminum molybdate may be formed as an intermediate, so the calcination temperature is preferably 500 to 1500°C, more preferably 600 to 1550°C, and even more preferably 700 to 1600°C.
[0122] The firing time is not particularly limited, but may be, for example, 1 minute to 30 hours, 10 minutes to 25 hours, or 100 minutes to 20 hours.
[0123] The heating rate varies depending on the molybdenum oxide precursor compound and the metal compound used, and the properties of the desired molybdenum trioxide particles, but from the viewpoint of production efficiency, the heating rate is preferably 0.1°C / min to 100°C / min, more preferably 1°C / min to 50°C / min, and even more preferably 2°C / min to 10°C / min.
[0124] The internal pressure in the calcination furnace is not particularly limited and may be positive pressure or reduced pressure, but from the viewpoint of suitably discharging the molybdenum oxide precursor compound from the calcination furnace to a cooling pipe, it is preferable to carry out the calcination under reduced pressure. A specific degree of reduced pressure is preferably -5000 Pa to -10 Pa, more preferably -2000 Pa to -20 Pa, and even more preferably -1000 Pa to -50 Pa. A degree of reduced pressure of -5000 Pa or more is preferable because it does not require excessive airtightness or mechanical strength of the calcination furnace, and it is possible to reduce the manufacturing cost. On the other hand, a degree of reduced pressure of -10 Pa or less is preferable because it is possible to prevent clogging of the molybdenum oxide precursor compound at the exhaust port of the calcination furnace.
[0125] When gas is blown into the firing furnace during firing, the temperature of the gas blown is preferably 5 to 500°C, and more preferably 10 to 100°C.
[0126] The gas blowing speed is preferably 1 L / min to 500 L / min, and more preferably 10 L / min to 200 L / min, relative to the effective volume of the firing furnace of 100 L.
[0127] The temperature of the vaporized molybdenum trioxide vapor varies depending on the type of molybdenum oxide precursor compound used, but is preferably 200 to 2000° C., and more preferably 400 to 1500° C. When the temperature of the vaporized molybdenum trioxide vapor is 2000° C. or lower, it usually tends to be easily granulated in a cooling pipe by blowing outside air (0 to 100° C.).
[0128] The discharge rate of molybdenum trioxide vapor discharged from the calcination furnace can be controlled by the amount of the molybdenum oxide precursor compound and the amount of the metal compound used, the temperature of the calcination furnace, the gas blown into the calcination furnace, and the diameter of the calcination furnace exhaust port. Although it varies depending on the cooling capacity of the cooling piping, the discharge rate of molybdenum trioxide vapor from the calcination furnace to the cooling piping is preferably 0.001 g / min or more and 100 g / min or less, and more preferably 0.1 g / min or more and 50 g / min or less.
[0129] The content of molybdenum trioxide vapor contained in the gas discharged from the calciner is preferably 0.01 mg / L or more and 1000 mg / L or less, and more preferably 1 mg / L or more and 500 mg / L or less.
[0130] The molybdenum trioxide vapor is then cooled and granulated. The molybdenum trioxide vapor is cooled by lowering the temperature of the cooling pipe. In this case, the cooling means may be, as described above, cooling by blowing gas into the cooling pipe, cooling by a cooling mechanism of the cooling pipe, or cooling by an external cooling device.
[0131] The molybdenum trioxide vapor is preferably cooled in an air atmosphere. By cooling the molybdenum trioxide vapor in an air atmosphere to form molybdenum trioxide particles, the ratio (I O / II O ) can be made larger than 1.1, and the β crystal structure of MoO3 is easily obtained in the molybdenum trioxide particles.
[0132] The cooling temperature (temperature of the cooling pipe) is not particularly limited, but is preferably from -100 to 600°C, and more preferably from -50 to 400°C.
[0133] The cooling rate of the molybdenum trioxide vapor is not particularly limited, but is preferably from 100° C. / s to 100,000° C. / s, and more preferably from 1,000° C. / s to 50,000° C. / s. Note that the faster the cooling rate of the molybdenum trioxide vapor, the smaller the particle size and the larger the specific surface area of the molybdenum trioxide particles that are obtained tend to be.
[0134] When the cooling means is a means for cooling by blowing gas into a cooling pipe, the temperature of the blown gas is preferably -100 to 300°C, and more preferably -50 to 100°C.
[0135] The gas flow rate is 0.1 m 3 / min or more 20m 3 / min or less is preferable, and 3 / min or more 10m 3 It is more preferable that the gas blowing speed is 0.1 m / min or less. 3 / min or more, a high cooling rate can be realized and clogging of the cooling pipes can be prevented, which is preferable. 3 / min or less is preferable because it eliminates the need for expensive first blowing means (exhaust fan, etc.), thereby enabling the manufacturing cost to be reduced.
[0136] The molybdenum trioxide vapor is cooled and the resulting particles are transported to a collector for recovery.
[0137] In the method for producing molybdenum trioxide particles, the molybdenum trioxide vapor may be cooled to obtain particles, which may be calcined again at a temperature of 100 to 320°C.
[0138] That is, the molybdenum trioxide particles obtained by the method for producing molybdenum trioxide particles may be calcined again at a temperature of 100 to 320°C. The calcination temperature of the second calcination may be 120 to 280°C, or 140 to 240°C. The calcination time of the second calcination may be, for example, 1 minute to 4 hours, 10 minutes to 5 hours, or 100 minutes to 6 hours. However, by calcining again, a part of the β crystal structure of molybdenum trioxide is lost, and when calcined at a temperature of 350°C or higher for 4 hours, the β crystal structure in the molybdenum trioxide particles is lost, the ratio (β(011) / α(021)) becomes 0, and the reactivity with sulfur is impaired. By the method for producing molybdenum trioxide particles described above, it is possible to produce molybdenum trioxide particles suitable for producing the composite.
[0139] [Cleaning process] The method for producing a composite according to the embodiment may include a washing step for removing the sulfur source after the calcination step. The washing step can remove the excess sulfur source used in the calcination step. The washing step may be repeated two or more times as necessary.
[0140] The method for removing the sulfur source is not particularly limited, but includes a method in which a solvent capable of dissolving the sulfur source is brought into contact with the product obtained in the calcination step to transfer the sulfur source to the solvent. The solvent may be toluene, hexane, carbon disulfide, etc., and the excess sulfur source can be removed by washing with the solvent.
[0141] For example, when elemental sulfur is used as the sulfur source, the content of elemental sulfur in the produced composite can be reduced by carrying out the washing step.
[0142] <Hydrogen generation catalyst> The composite of the embodiment can be suitably used as a catalyst in the hydrogen generation reaction (HER) (sometimes referred to as "hydrogen generation catalyst" in this specification). The composite of the embodiment can also be used as a hydrogen generation catalyst when used in combination with a conductive material. That is, a preferred hydrogen generation catalyst is, for example, one that contains the composite of the embodiment, and the hydrogen generation catalyst may further contain a conductive material in addition to the composite of the embodiment. The catalytic activity of the hydrogen generation catalyst in the hydrogen generation reaction (HER) that contains the composite of the embodiment and a conductive material is higher.
[0143] The conductive material may be any known material. Examples of the conductive material include carbon and metals, which have high conductivity. The hydrogen generation catalyst may contain only one type of conductive material, or may contain two or more types of conductive materials.
[0144] Examples of the conductive material include carbon black such as acetylene black, Cabot carbon black, and Ketjen black, graphite, carbon fiber, metal powder, etc. Ketjen black has a high specific surface area and electrical conductivity, and is also excellent in that it can suppress the aggregation of molybdenum sulfide.
[0145] Examples of the metal that is the conductive material include gold, silver, copper, aluminum, rhodium, molybdenum, tungsten, iron, nickel, cobalt, and indium.
[0146] The hydrogen generation catalyst may contain only one type of metal as a conductive material, or may contain two or more types of metal.
[0147] The hydrogen generation catalyst may, for example, contain no metal but contain carbon as a conductive material, may contain no carbon but contain a metal, or may contain both a metal and carbon.
[0148] In the hydrogen generation catalyst, the content of the conductive material is preferably 0.1 to 100 parts by mass, and more preferably 0.5 to 50 parts by mass, relative to 100 parts by mass of the content of the composite of the embodiment.
[0149] In the hydrogen generation catalyst, the ratio of the total content of the composite of the embodiment and the conductive material to the total mass (100 mass%) of the hydrogen generation catalyst is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more, and may be, for example, any of 97 mass% or more and 99 mass% or more, or may be 100 mass%. When the ratio is equal to or more than the lower limit, the catalytic activity of the hydrogen generation catalyst in the hydrogen generation reaction (HER) becomes higher. The ratio may be 100 mass% or less.
[0150] <Catalyst ink> The hydrogen generating catalyst is suitable as a component contained in a catalyst ink. The catalyst ink of the embodiment contains the complex of the embodiment and a solvent. The catalyst ink of the embodiment may contain the composite of the embodiment, a polymer electrolyte, and a solvent.
[0151] The catalyst ink of this embodiment may further contain a conductive material. The type and content of the conductive material may be those exemplified above.
[0152] The catalyst ink can be applied to, for example, a working electrode substrate to form a catalyst layer.
[0153] The polymer electrolyte may be one generally used in the formation of a catalyst layer.Specific examples of the polymer electrolyte include perfluorocarbon polymers having sulfonic acid groups (e.g., Nafion (registered trademark)), hydrocarbon polymer compounds having sulfonic acid groups, polymer compounds doped with inorganic acids such as phosphoric acid, organic / inorganic hybrid polymers partially substituted with proton-conductive functional groups, and proton conductors in which a polymer matrix is impregnated with a phosphoric acid solution or a sulfuric acid solution.
[0154] Examples of the solvent include a solvent capable of dispersing the composite of the embodiment and capable of forming a catalyst layer by applying the solvent to a working electrode substrate, etc. The solvent preferably contains an alcohol such as 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 1-heptanol, or 2-heptanol. EXAMPLES
[0155] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0156] [Synthesis Example 1] (Production of molybdenum trioxide particles) A calcination furnace equivalent to a heat-resistant container, a cooling pipe with an external air supply port, and a dust collector for collecting molybdenum oxide were prepared. Molybdenum oxide was produced using an RHK simulator (manufactured by Noritake Co., Ltd.) as the calcination furnace and a VF-5N dust collector (manufactured by Amano Corporation) as the dust collector. 1.5 kg of aluminum hydroxide (manufactured by Nippon Light Metals Co., Ltd.) and 1 kg of molybdenum trioxide (manufactured by Nippon Muki Co., Ltd.) were mixed and then charged into a sagger. The firing furnace was connected to a cooling pipe and a dust collector, and the mixture was fired at a temperature of 1100°C for 10 hours. During firing, outside air (air flow rate: 150 L / min, outside air temperature: 25°C) was introduced from the side and bottom of the firing furnace. After evaporating in the furnace, molybdenum trioxide was cooled near the dust collector and precipitated as particles, and the molybdenum trioxide was collected by the dust collector. After calcination, 1.0 kg of blue powder aluminum oxide was taken out from the scabbard and 0.8 kg of molybdenum trioxide was collected in a dust collector. The recovered molybdenum trioxide had a primary particle size of 1 μm or less, and fluorescent X-ray measurement confirmed that the purity of the molybdenum trioxide was 99.8%.
[0157] [Example 1] (Production of Composite Particles) 500 mg of the molybdenum trioxide particles obtained in the above Synthesis Example 1 and 556 mg of sulfur (Kanto Chemical Co., Ltd. Reagent, S) were put into a crucible and mixed uniformly. The amount of S in sulfur was 5 moles per mole of MoO3 in the molybdenum trioxide particles used. After mixing, the crucible was covered with a lid and put into a nitrogen atmosphere furnace for firing. The firing conditions were that the temperature was raised from room temperature of 25°C at a rate of 5°C / min, and the temperature was maintained for 4 hours after reaching 300°C. During the firing process, nitrogen gas was blown at 0.2 ml / min. Thereafter, the temperature in the furnace was lowered by natural cooling to obtain a product. The obtained product was ultrasonically cleaned in toluene, and then the cleaning work of exchanging the toluene was performed three times, and then vacuum dried to obtain the composite particles of Example 1.
[0158] [Examples 2 to 5] Composite particles of Examples 2 to 5 were obtained in the same manner as in Example 1 above, except that the amounts of sulfur used as raw materials and the firing temperature were as shown in Table 1.
[0159] [Reference example 1] Particles of Comparative Example 1 were obtained in the same manner as in Example 1 above, except that the firing temperature in Example 1 was set to the conditions shown in Table 1.
[0160] [Reference example 2] The molybdenum trioxide particles obtained in Synthesis Example 1 were used as molybdenum trioxide particles of Reference Example 2.
[0161] [Comparative Example 1] Commercially available molybdenum trioxide particles (manufactured by Nippon Inorganic Chemical Industry Co., Ltd.) were used as the molybdenum trioxide particles of Comparative Example 1.
[0162] [Comparative Example 2] Commercially available molybdenum disulfide particles (manufactured by Kanto Chemical Co., Ltd.) were used as the molybdenum disulfide particles of Comparative Example 2.
[0163] The particles of Examples 1 to 5, Reference Examples 1 and 2, and Comparative Examples 1 and 2 were used as samples and the following evaluations were carried out.
[0164] Evaluation [XRF analysis] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), about 20-30 mg of the sample was placed on filter paper and covered with PP film for composition analysis. From the amount of sulfur determined from the XRF analysis results, the molybdenum disulfide equivalent amount (mass%) relative to 100% mass of the sample particles was calculated. From the amount of molybdenum obtained by subtracting the molybdenum equivalent of molybdenum disulfide, the molybdenum trioxide equivalent amount (mass%) relative to 100% mass of the sample particles was calculated.
[0165] [XRD crystal structure measurement] The sample was loaded into a measurement sample holder with a depth of 0.5 mm and set in a wide-angle X-ray diffraction (XRD) device (Ultima IV, manufactured by Rigaku Corporation). Measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, scan speed 2θ = 2° / min, and scan range 2θ = 10° to 70°.
[0166] [Crystallite size measurement] The measurement was performed using a SmartLab 9kW (Rigaku Corporation) as an X-ray diffraction device, a scintillation counter detector as a detector, and PDXL2 as analysis software. The measurement method was the 2θ / θ method, and the average crystallite size of molybdenum disulfide was calculated using the Scherrer formula from the half-width of the peak appearing at 2θ=14.4°±0.5°. The average crystallite size of molybdenum trioxide was calculated using the Scherrer formula from the half-width of the peak appearing at 2θ=12.7°±0.5°. The measurement conditions were a scan speed (2θ) of 2.0° / min, a scan range (2θ) of 10 to 70°, a step (2θ) of 0.02°, and no standard width of the device.
[0167] [Conversion rate R C ] Conversion rate of the sample to MoS2 R C was calculated by the RIR (reference intensity ratio) method from the profile data obtained by measuring the sample by X-ray diffraction (XRD). The RIR value K of molybdenum disulfide (MoS2) Aand the integrated intensity I of the peak at 2θ=14.4°±0.5°, which is assigned to the (002) or (003) plane of molybdenum disulfide (MoS2). A , and each molybdenum oxide (the raw material MoO3 and the reaction intermediate Mo9O 25 , Mo4O 11 , MoO2, etc.) RIR value K B and each molybdenum oxide (the raw material MoO3 and the reaction intermediate Mo9O 25 , Mo4O 11 , MoO2, etc.) B Using the above, the conversion rate R to MoS2 is calculated from the following equation (1): C R C (%)=(I A / K A ) / ((I A / K A )+Σ(I B / K B ))×100 (1) Here, the RIR values used were those listed in the Inorganic Crystal Structure Database (ICSD) (manufactured by the Japan Chemical Information Association), and the analysis was performed using integrated powder X-ray analysis software (PDXL2, manufactured by Rigaku Corporation).
[0168] [Measurement of BET specific surface area] The specific surface area was measured using a specific surface area meter (Microtrack-Bel, BELSORP-mini), and the surface area per gram of sample measured from the amount of nitrogen gas adsorbed by the BET method was calculated as the specific surface area.
[0169] [Median diameter D 50 Measurement of 0.1 g of sample powder was added to 20 cc of acetone, and ultrasonicated in an ice bath for 4 hours. The concentration was then adjusted with acetone to a suitable range within the measurable range of a dynamic light scattering particle size distribution analyzer (Microtrack Bell, Nanotrac WaveII) to obtain a measurement sample. Using this measurement sample, the particle size distribution in the particle size range of 0.0001 μm to 10 μm was measured with the dynamic light scattering particle size distribution analyzer, and the median diameter D50 The median diameter D 50 For those having a particle diameter of more than 10 μm (Comparative Example 2), a solution was prepared in the same manner, and the particle diameter distribution in the particle diameter range of 0.015 μm to 500 μm was measured using a laser diffraction particle size distribution measuring device (Shimadzu Corporation, SALD-7000). 50 was calculated.
[0170] The results of the above measurements are shown in Table 1.
[0171] [Table 1]
[0172] The particles of Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1 to 2 have the MoO3 content, MoS2 content, and conversion rate R C , BET specific surface area, MoS2 average crystallite size, MoO3 average crystallite size, and D 50 had the following characteristics:
[0173] The results of the XRD analysis are shown in FIG. 2. The XRD profiles of the composite particles of Examples 1 to 5 included both peaks attributable to MoS2 and peaks attributable to MoO3. In addition, from the XRD profiles of the particles of Examples 1 to 5 and Reference Example 1, peaks at 2θ=39.5° and 49.5° derived from the 2H crystal structure of MoS2, and peaks at 2θ=32.5°, 39.5°, and 49.5° derived from the 3R crystal structure of MoS2 were confirmed. It was confirmed that the particles of Examples 1 to 5 and Reference Example 1 included the 2H crystal structure and 3R crystal structure of MoS2.
[0174] FIG. 3 shows an observation image of the composite particle of Example 1 obtained with a transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400).
[0175] FIG. 4 shows an HAADF-STEM image (transmission electron image, JEM-ARM300F, manufactured by JEOL Ltd.) of the composite particle of Example 1 and the results of element mapping by energy dispersive X-ray spectroscopy (EDS). The results of element mapping showed that there were regions with low abundance of O element and high abundance of S element on the surface and near the surface of the composite particle (see the arrow in Figure 3). In other words, the closer to the surface of the composite particle, the higher the content of MoS2 than MoO3, and MoS2 was unevenly distributed on the surface of the composite particle. This suggested the possibility that MoO3 of the particles of Synthesis Example 1, the raw material, was converted to MoS2 in the firing process, starting from the surface layer in contact with the sulfur source.
[0176] (Catalyst ink manufacturing) Inks were produced using the particles of each of Examples 1 to 5, Reference Examples 1 and 2, and Comparative Examples 1 and 2 as raw materials, and their catalytic performance in the hydrogen evolution reaction (HER) was evaluated by the following method.
[0177] 4 mg of the particles obtained above (any of the particles of Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1 to 2) and carbon black (Ketjen Black, manufactured by Lion Specialty Chemicals Co., Ltd., product number: EC300J, median diameter D 50 An ink (dispersion) was produced by mixing 2 mg of 1000 nm (40 nm), 40 μL of 5% Nafion dispersion (FUJIFILM Wako Pure Chemical Industries, Nafion dispersion solution), and 1 mL of ethanol, and dispersing the particles by ultrasonic treatment for 1 hour. 20 μL of the obtained ink was applied to the electrode surface, and the surface liquid was naturally dried, then transferred to a vacuum dryer and dried at 60 °C for 6 hours or more to obtain a test electrode. The hydrogen evolution reaction (HER) activity of the obtained test electrode was evaluated using a three-electrode method. The evaluation conditions were an LSV method with a scan voltage range of -0.3 V to 0 V and a scan speed of 5 mV / S.
[0178] The evaluation results of the above catalyst performance are shown in Table 1.
[0179] The inks containing the composite particles of Examples 1 to 5 had a current density of 10 mAcm compared to the inks containing the particles of Reference Examples 1 to 2 or Comparative Examples 1 to 2. -2 The overvoltage value at −0.3 V was low (measurement was not possible in Reference Example 2 and Comparative Examples 1 and 2), and the current density value at −0.3 V was high.
[0180] From the above, it was demonstrated that the composites of Examples 1 to 5 were capable of exhibiting excellent hydrogen generation catalytic activity.
[0181] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims. [Explanation of symbols]
[0182] 1 Manufacturing equipment 2. Firing furnace 3 Cooling piping 4. Collection Machine 5. Exhaust port 6 Opening adjustment damper 7 Observation window 8 Ventilation device 9 External cooling device
Claims
1. A composite material comprising molybdenum disulfide and molybdenum trioxide, the molybdenum disulfide comprises a 3R crystal structure; A composite, wherein the content of a molybdenum trioxide equivalent value (B) calculated from the molybdenum content determined by XRF analysis of the composite is 10.8 to 69.7 mass% relative to the total mass of the composite, the content of a molybdenum disulfide equivalent value (A) calculated from the sulfur content determined by XRF analysis of the composite is 89.2 to 30.3 mass% relative to the total mass of the composite, and the sum of the molybdenum disulfide equivalent value (A) and the molybdenum trioxide equivalent value (B) is 100 mass%.
2. 2. The composite according to claim 1, wherein the molybdenum disulfide has an average crystallite size of 50 nm or less, as determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.
3. 3. The complex according to claim 1, wherein the molybdenum trioxide has an average crystallite size of 50 nm or less, as determined from a peak at 2θ=12.7°±0.5 obtained by X-ray diffraction measurement.
4. The median diameter D of the complex determined by dynamic light scattering 50 The complex according to claim 1 or 2, wherein the diameter of the complex is 1000 nm or less.
5. The specific surface area of the composite, as measured by the BET method, is 5 m 2 / g or more 200m 2 The complex according to claim 1 or 2, wherein the molecular weight is 1 / g or less.
6. 3. The composite according to claim 1, wherein the ratio of the content of sulfur as an element to the total content of sulfur element in the composite is 10% or less on a molar basis.
7. A hydrogen generation catalyst comprising the composite according to claim 1 or 2.
8. The hydrogen generation catalyst according to claim 7 , further comprising a conductive material.
9. A catalyst ink comprising the composite according to claim 1 or 2 and a solvent.
10. 10. The catalyst ink of claim 9 further comprising a polyelectrolyte.
11. The catalyst ink of claim 9 further comprising a conductive material.
12. 3. A method for producing the composite according to claim 1, further comprising a calcination step of heating molybdenum trioxide in the presence of a sulfur source at a temperature of 400° C. or less.
13. The method for producing a composite according to claim 12, further comprising, after the calcination step, a washing step for removing the sulfur source.
14. The specific surface area of the molybdenum trioxide measured by the BET method is 10 m 2 / g or more 100m 2 The method for producing the composite according to claim 13, wherein the molecular weight of the composite is 1 / g or less.
Citation Information
Patent Citations
Three-dimensional nano molybdenum-based lithium ion battery negative electrode material and preparation method thereof
CN114560502A
Molybdenum disulfide nanoflower and its manufacturing method
JP2004277199A
Method and apparatus for the production of inorganic fullerene-like nanoparticles
JP2004512250A
Regenerated hydrotreating catalyst
JP2011143389A
Molybdenum sulfide, method for producing same and hydrogen generation catalyst
WO2019181723A1
